2009
DOI: 10.1021/jp809687v
|View full text |Cite
|
Sign up to set email alerts
|

SERS Enhancement Factors Studies of Silver Nanoprism and Spherical Nanoparticle Colloids in The Presence of Bromide Ions

Abstract: Surface-enhanced Raman Scattering (SERS) of R6G has been observed in two different silver colloids in the presence of KBr. It was found in spherical nanoparticles with an average diameter of 10 ( 2 nm and in their photoinduced conversion products with sodium light irradiation, silver nanoprisms, with an average edge length of 70 ( 30 nm and thickness of about 10 ( 2 nm. The SERS intensity of R6G (4.5 × 10 -9 M) in the silver nanoprism colloid was 20× stronger than in the spherical nanoparticle colloid with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 36 publications
(68 reference statements)
8
96
0
4
Order By: Relevance
“…Near-field localization and studies of SERS on a variety of plasmonic structures have been reported previously by various researchers [11][12][13][14][15]. It is also reported that twodimensional (2D) structures are superior compared to onedimensional (1D) structure.…”
Section: Introductionmentioning
confidence: 73%
“…Near-field localization and studies of SERS on a variety of plasmonic structures have been reported previously by various researchers [11][12][13][14][15]. It is also reported that twodimensional (2D) structures are superior compared to onedimensional (1D) structure.…”
Section: Introductionmentioning
confidence: 73%
“…As a result, due to adsorption of an analyte the scattering characteristic of an incident light would improve with respect to silver atom alone [15]. In this regard, determining quantitative parameters, namely the analytical enhancement factor (AEF) and surface enhancement factor (SEF) are of great interest [16,17]. Pavel et al [14] used these values to determine the adsorption of rodamine 6G, a fluorescent dye, through optical characteristics of the colloidal AgNPs via an increase in SERS signals as compared to the normal Raman.…”
Section: Dielectric and Optical Properties Of Agnpsmentioning
confidence: 99%
“…[174] Auch postsynthetische Methoden für die Modifikation von trigonalen Ag-Prismen wurden entwickelt. Hierbei wurden die Spitzen durch Einwirkung von Wärme, [175][176][177] Säuren, [178] Halogeniden [179][180][181][182] oder durch andere chemische Additive abgeätzt. [183,184] Auch wenn diese Methoden nicht Gegenstand dieses Aufsatzes sind, wollen wir hier ein Verfahren, das auf UV-Belichtung beruht, kurz näher erläutern.…”
Section: Zirkulare Und Hexagonale Plättchenunclassified